Investigating the Challenges Faced by EFL Teachers in Remote Teaching During COVID-19 Emergencies at Indonesian Senior High School Context: A Qualitative Descriptive Study - Ni Made Desi Puspasari; IGA Lokita Purnamika Utami; Luh Gd Rahayu Budiarta (ELT Worldwide: Journal of English Language Teaching, 2023)
The COVID-19 pandemic has prompted a rapid shift from traditional face-to-face teaching to remote learning in educational institutions worldwide, including Indonesian senior high schools. This qualitative descriptive study explores the challenges faced by English as a Foreign Language (EFL) teachers during this transition, focusing on technology infrastructure, student engagement, assessment, and adapting teaching methods. The data were collected through semi-structured interviews with two English teachers who teach at XII and XI grade at Sma Negeri 1 Seririt and Smk Karya Usada in Buleleng regency. The findings reveal that EFL teachers experienced difficulties in accessing and utilizing technology, maintaining student engagement, developing and administering effective assessments, and adapting their teaching methods and materials for remote instruction. The findings provide valuable insights into the experiences of EFL teachers during the pandemic, as well as recommendations for overcoming these challenges, including improving technology infrastructure, enhancing student engagement, developing new assessment methods, and providing professional development opportunities for EFL teachers. This research contributes to the understanding of the impact of the COVID-19 pandemic on EFL education in Indonesia and offers a foundation for future studies and policy-making in the area of remote EFL teaching.